Clinical Features of High-Grade Extremity and Trunk Sarcomas in Patients Aged 80 Years and Older: Why Are Outcomes Inferior? - Imanishi, Jungo; Chan, Lester W. M.; Broadhead, Matthew L.; Pang, Grant; Ngan, Samuel Y.; Slavin, John; Sharp, Stephen; Choong, Peter F. M. (Frontiers in Surgery, 2019)
Background: The population of many countries is aging and a significant number of elderly patients with soft-tissue sarcoma are being seen at cancer centers. The unique therapeutic and prognostic implications of treating soft-tissue sarcoma in geriatric patients warrant further consideration in order to optimize outcomes. Patients and Methods: This is a single-institution retrospective study of consecutive non-metastatic primary extremity and trunk high-grade sarcomas surgically treated between 1996–2012, with at least 2 years of follow-up for survivors. Patient characteristics and oncological outcomes were compared between age groups (≥80 years vs. <80 years), using Chi-square or Fisher-exact test and Log-Rank or Wilcoxon test respectively. Deaths from other causes were censored for disease-specific survival estimation. A p-value of less than 0.05 was regarded as statistically significant. Results: A total of 333 cases were eligible for this study. Thirty-six patients (11%) were aged ≥80 years. Unplanned surgery incidence and surgical margin status were comparable between the age groups. Five-year local-recurrence-free, metastasis-free and disease-specific survivals were 72% (≥80 years) vs. 90% (<80 years) (p = 0.004), 59% vs. 70% (p = 0.07) and 55% vs. 80% (p< 0.001), respectively. A significantly earlier first metastasis after surgery (8.3 months vs. 20.5 months, mean) and poorer survival after first metastasis (p = 0.03) were observed. Cox analysis revealed ‘age ≥80 years’ as an independent risk factor for local failure and disease-specific mortality, with hazard ratios of 2.41 (95% CI: 1.09–5.32) and 2.52 (1.33–4.13) respectively. A competing risks analysis also showed that ‘age ≥80 years’ was significantly associated with the disease-specific mortality. Conclusions: Oncological outcomes were significantly worse in high-grade sarcoma patients aged ≥80 years. The findings of more frequent local failure regardless of a consistent primary treatment strategy, an earlier time to first metastasis after surgery, and poorer prognosis after first metastasis suggest that more aggressive tumor biology, in addition to multiple co-morbidity, may explain the inferiority.